Red‐light receptor phytochrome B inhibits BZR1‐NAC028‐CAD8B signaling to negatively regulate rice resistance to sheath blight. (9th December 2022) - Yuan, De Peng; Yang, Shuo; Feng, Lu; Chu, Jin; Dong, Hai; Sun, Jian; Chen, Huan; Li, Zhuo; Yamamoto, Naoki; Zheng, Aiping; Li, Shuang; Yoon, Hong Chan; et al.
Abstract: Phytochrome (Phy)‐regulated light signalling plays important roles in plant growth, development, and stress responses. However, its function in rice defence against sheath blight disease (ShB) remains unclear. Here, we found that PhyB mutation or shade treatment promoted rice resistance to ShB, while resistance was reduced by PhyB overexpression. Further analysis showed that PhyB interacts with phytochrome‐interacting factor‐like 15 (PIL15), brassinazole resistant 1 (BZR1), and vascular plant one‐zinc‐finger 2 (VOZ2). Plants overexpressing PIL15 were more susceptible to ShB in contrast to bzr1‐D‐ overexpressing plants compared with the wild‐type, suggesting that PhyB may inhibit BZR1 to negatively regulate rice resistance to ShB. Although BZR1 is known to regulate brassinosteroid (BR) signalling, the observation that BR signalling negatively regulated resistance to ShB indicated an independent role for BZR1 in controlling rice resistance. It was also found that the BZR1 ligand NAC028 positively regulated resistance to ShB. RNA sequencing showed that cinnamyl alcohol dehydrogenase 8B ( CAD8B ), involved in lignin biosynthesis was upregulated in both bzr1‐D‐ and NAC028 ‐overexpressing plants compared with the wild‐type. Yeast‐one hybrid, ChIP, and transactivation assays demonstrated that BZR1 and NAC028 activate CAD8B directly. Taken together, the analyses demonstrated that PhyB‐mediated light signalling inhibits the BZR1‐NAC028‐CAD8B pathway to regulate rice resistance to ShB. Summary Statement: Phytochrome B mutation‐mediated shading condition increased rice resistance to sheath blight. In the light, Phytochrome B translocated from cytosol to nucleus where it interacts with and inhibits BZR1 function. BZR1 interacts with NAC028 to directly activate CAD8B to increase lignin contents by which rice resistance to sheath blight.